Analysis of Land Disputes Between PT Freeport Indonesia, the Indonesian Government and the Papuan Community - Tsaqif, Achmad Muflihuts; Situmorang, Leonard Roderick; Rajabi, Zalfa; Yayi Tarina, Dwi Desi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The land dispute between PT Freeport Indonesia, the Indonesian Government, and the Papuan community has been a long-standing issue with significant economic, environmental, and social implications. This analysis delves into the complexities of the conflict, exploring the historical context, legal frameworks, and the perspectives of all parties involved. It examines the root causes of the dispute, the environmental and social impacts of Freeport's operations, and the challenges in finding a resolution that balances economic interests with environmental protection and community rights. The analysis also investigates the role of the Indonesian Government as a mediator and regulator, and the efforts made to address the concerns of the Papuan community. Ultimately, this comprehensive analysis aims to provide insights and recommendations for a fair and sustainable resolution to this complex land dispute.